PERAN KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH TERHADAP MUTU KINERJA MENGAJAR GURU DI SMP N 3 BOJA - Rias Dewi Setyowati; Noor Miyono (STKIP Subang, 2024)
This research report explains optimizing the quality of teacher teaching performance at SMP Negeri 3 Boja, Boja District. The quality of teacher teaching performance is an important element in achieving good quality education. The increasingly urgent demand for teachers who are qualified and perform optimally in carrying out their roles and duties as educators has implications for the need for efforts to develop teacher performance on an ongoing basis. The aim of this research is to describe and analyze the influence of the principal's instructional leadership on the quality of teaching performance of teachers at SMP Negeri 3 Boja, Boja District. The method used is a survey method with a quantitative approach. The total research sample was 35 teachers and 98 class VII students. The data collection technique uses a questionnaire. Data were analyzed through correlation and regression analysis. The research results show that the quality of teachers' teaching performance is in the high category, the principal's instructional leadership is in the high category. Partially, the principal's instructional leadership has a positive effect on the quality of teacher teaching performance. Furthermore, simultaneously, it also has a positive and significant effect on the quality of teacher teaching performance.